Adsorption of red cabbage dye through of coal from pequi bark (Caryocar brasiliense) - Lopes, Toni Jefferson; Ávila, Mariana Ferreira; Lima, Luciana Costa (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
Adsorption is a surface phenomenon operation involves a contact between fluid and solid phases, as a result, a mass transfer from the fluid phase to the solid surface. The charcoal is one of the most utilized materials for this purpose. Some agricultural and industrial waste, due to the common existence of carbon in its composition, can be used for this purpose, avoiding its disposal on the environment. As an example, the ‘Pequi’ rind could be used as an alternative charcoal adsorbent, allowing a technology aggregation and value for this byproduct. The present work aimed to study the anthocyanins adsorption from red cabbage extract through the charcoal made from ’Pequi’ rind. The results obtained were: The DSC and TGA characterization, the peak of the exothermic sample was around 440 °C and it was obtained a residual amount of inorganic compounds of 3.173%. In the tests of the kinetic, the equilibrium time was 150 minutes for different concentrations of dye and the determination of Langmuir and Freundlich isotherms parameters, the best results were obtained using the Freudnlich model. As a conclusion from the overall results, the ‘Pequi’ rind could be used as an alternative for red cabbage dye separation (red cabbage anthocyanins) of sugar for food purposes.